2021
DOI: 10.14814/phy2.14754
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent decrease in TRPM4 channel expression but not trafficking alters urinary bladder smooth muscle contractility

Abstract: During development, maturation, or aging, the expression and function of urinary bladder smooth muscle (UBSM) ion channels can change, thus affecting micturition. Increasing evidence supports a novel role of transient receptor potential melastatin‐4 (TRPM4) channels in UBSM physiology. However, it remains unknown whether the functional expression of these key regulatory channels fluctuates in UBSM over different life stages. Here, we examined TRPM4 channel protein expression (Western blot) and the effects of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The modest CBA‐induced inhibition observed at the highest concentrations likely reflects non‐selectivity 36 . In contrast, 9‐phenanthrol strongly inhibited guinea pig UBSM contractility 3,13,15 . In our experiments, the maximum concentration of DMSO to dissolve CBA was 0.3% (v/v).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The modest CBA‐induced inhibition observed at the highest concentrations likely reflects non‐selectivity 36 . In contrast, 9‐phenanthrol strongly inhibited guinea pig UBSM contractility 3,13,15 . In our experiments, the maximum concentration of DMSO to dissolve CBA was 0.3% (v/v).…”
Section: Discussionmentioning
confidence: 68%
“…The isometric UBSM tension recording experiments were conducted as previously described. 3,13,15 Briefly, UBSM strips were clipped between a stationary mount and a force-displacement transducer and then placed in tissue baths filled with Ca 2+containing physiological salt solution (PSS) thermostatically controlled at 37°C. UBSM strips were stretched to an initial level of ~10 mN (1 g) and washed with fresh PSS every 15 min for 45-60 min equilibration period.…”
Section: Isometric Ubsm Tension Recordingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Provence et al suggested a spatial and functional coupling between TRPM4 channels and IP3 receptors in detrusor smooth muscle cells obtained from healthy humans [171]. Moreover, in guinea pigs, an overall reduction of the TRPM4 protein was reduced during aging and in line with that, the action of 9-phenanthrol (inhibition of the amplitude and muscle force of spontaneous and KCl-induced phasic contractions) was less pronounced in adult animals compared with juvenile ones [176].…”
Section: Trpm4 In Urinary Bladdermentioning
confidence: 93%